2015
DOI: 10.1179/1754762815y.0000000015
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation: An assessment of quality and readability of web-based information aimed at patients

Abstract: Internet-based information regarding cochlear implantation is of varied quality and is written above the expected reading level of an average person.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 5 publications
2
25
0
Order By: Relevance
“…This evaluation demonstrates that most consumer health information websites about anal cancer are of low quality and require readers to have high health literacy. This is consistent with previous evaluations of online patient information for a diverse range of other medical conditions [3138]. Only the Cancer Research UK website met plain language best practices and was rated “good” quality [54].…”
Section: Discussionsupporting
confidence: 87%
“…This evaluation demonstrates that most consumer health information websites about anal cancer are of low quality and require readers to have high health literacy. This is consistent with previous evaluations of online patient information for a diverse range of other medical conditions [3138]. Only the Cancer Research UK website met plain language best practices and was rated “good” quality [54].…”
Section: Discussionsupporting
confidence: 87%
“…Forty-two percent (36/85) of PEMs had total DISCERN scores corresponding to "poor" or "very poor" quality. Seymour et al demonstrated similar results when evaluating the quality of web-based patient information on cochlear implantation which revealed that 63% of websites scored as "poor" or "very poor" quality based on total DISCERN scores [19]. In addition to overall scores, looking at the subdomains and individual questions within the DISCERN tool, can highlight more specific deficiencies in the PEMs.…”
Section: Discussionmentioning
confidence: 82%
“…However, studies have shown that online PEMs are often written at a much higher literacy level [13][14][15][16]. Within the realm of otolaryngology-head and neck surgery (OHNS), several studies have revealed that online information on OHNS procedures and conditions are written above the recommended grade level and are lacking in terms of quality [17][18][19][20][21][22][23]. Since septoplasty is a common OHNS procedure, it is important that clinicians evaluate the information patients are accessing online about their surgery.…”
Section: Introductionmentioning
confidence: 99%
“…For the discipline of otorhinolaryngology, 21 investigations on diseases and 18 on procedures simulated the search queries for online health information performed by laypeople and analyzed the quality of the resulting output. The topics of oncology [103][104][105][106][107][108], audiology/neurootology/otology [109][110][111][112][113][114][115][116][117], and plastic surgery [118][119][120][121][122] were most frequently represented. So far, available studies are focused predominantly on content in English.…”
Section: Investigationsmentioning
confidence: 99%
“…In all trials performed up to now, Google was used as search engine. Additionally, Bing [103,109,113,114,118,[124][125][126][127], Yahoo [103-105, 109, 113, 114, 118, 124-130], HONsearch [104], Med-linePlus [105], MSN, AOL, and Ask Jeeves [130] as well as omnimedicalsearch.com, pogofrog.com, searchmedica.co.uk, and imedisearch.com [125] were applied. The readability of the retrieved material according to the Flesch Reading Ease Score amounted to 29.7-61.5 [103, 104, 106-109, 112, 114, 115, 118, 122, 126, 130-139].…”
Section: Investigationsmentioning
confidence: 99%